Preclinical validation of NeoWarm, a low-cost infant warmer and carrier device, to ameliorate induced hypothermia in newborn piglets as models for human neonates - Bluhm, Nick D. P.; Tomlin, Grant M.; Hoilett, Orlando S.; Lehner, Elena A.; Walters, Benjamin D.; Pickering, Alyson S.; Bautista, Kevin Alessandro; Bucher, Sherri L.; Linnes, Jacqueline C. (Frontiers in Pediatrics, 2024)
Introduction: Approximately 1.5 million neonatal deaths occur among premature and small (low birthweight or small-for gestational age) neonates annually, with a disproportionate amount of this mortality occurring in low-and middle-income countries (LMICs). Hypothermia, the inability of newborns to regulate their body temperature, is common among prematurely born and small babies, and often underlies high rates of mortality in this population. In high-resource settings, incubators and radiant warmers are the gold standard for hypothermia, but this equipment is often scarce in LMICs. Kangaroo Mother Care/Skin-to-skin care (KMC/STS) is an evidence-based intervention that has been targeted for scale-up among premature and small neonates. However, KMC/STS requires hours of daily contact between a neonate and an able adult caregiver, leaving little time for the caregiver to care for themselves. To address this, we created a novel self-warming biomedical device, NeoWarm, to augment KMC/STS. The present study aimed to validate the safety and efficacy of NeoWarm.Methods: Sixteen, 0-to-5-day-old piglets were used as an animal model due to similarities in their thermoregulatory capabilities, circulatory systems, and approximate skin composition to human neonates. The piglets were placed in an engineered cooling box to drop their core temperature below 36.5 °C, the World Health Organizations definition of hypothermia for human neonates. The piglets were then warmed in NeoWarm (n=6) or placed in the ambient 17.8 ± 0.6 °C lab environment (n=5) as a control to assess the efficacy of NeoWarm in regulating their core body temperature.Results: All 6 piglets placed in NeoWarm recovered from hypothermia, while none of the 5 piglets in the ambient environment recovered. The piglets warmed in NeoWarm reached a significantly higher core body temperature (39.2 ± 0.4 o C, n=6) than the piglets that were warmed in the ambient environment (37.9 ± 0.4 o C, n=5) (p < 0.001). No piglet in the NeoWarm group suffered signs of burns or skin abrasions.Discussion: Our results in this pilot study indicate that NeoWarm can safely and effectively warm hypothermic piglets to a normal core body temperature and, with additional validation, shows promise for potential use among human premature and small neonates.